PENETAPAN HARGA KAMAR BATIQA HOTEL PEKANBARU - Pasaribu, Juana; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The development of the hospitality industry in the city of Pekanbaru is currently growing, we can see this from the many hotels in the city of Pekanbaru. Batiqa Hotel is one of the three-star hotels (***) of the many star-rated hotels in Pekanbaru City. The number of hotels in the city of Pekanbaru resulted in very tight competition, the increasing competition in controlling the market, requiring each hotel to be more careful in determining the price of its products in order to get the best position in market share. Therefore, the purpose of this study is to find out how far the factors (competition, demand elasticity, and cost structure) influence the price setting of rooms at Batiqa Hotel Pekanbaru. Based on the method used is a qualitative method with a descriptive approach, the data in this study were collected through interviews and observations with the management of Batiqa Hotel Pekanbaru. Based on the data analysis carried out, it turns out that competition factors, demand elasticity, and cost structure are very dominant influencing the decision on room price determination of Batiqa Hotel Pekanbaru. Keywords : Competition, Demand Elasticity, Cost Structure, Price, Hotel